IDENTIFIKASI DAN ANALISIS MODAL SOSIAL DALAM RANGKA PEMBERDAYAAN MASYARAKAT NELAYAN DESA GANGGA DUA KABUPATEN MINAHASA UTARA - Pontoh, Otniel (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
This research which aimed to identified and analyzed social capital of fisheries communities in Gangga dua village, North Monahasa District, has been conducted in 2007. Socio-culture data collected from fisheries community is consist of local value and local value system, local religious, pattern and system of production and reproduction and local politics. Data was collected by snowball sampling from community members who have deep knowledge about socio-culture of their community themselves. After data collected shown the socio-culture character of fisheries community then it has been analyzed to show the social capital typology. The research shows that fisheries community in Gangga Dua village still become closed community or has a characteristif of social capital bounding. Need a policy related to social structure improvement because of the social capital typology's of fisheries community in Pasauran village has been big influenced by various of economic aspect in economic activity of their life.